بيان المجمع الفاتيكاني الثاني ومبادرة الحوار الإسلامي – المسيحي - جوادة, خديجة (جامعة الوادي - University of Eloued, 2022)
يتناول هذا البحث المبادرة التي جاء بها الفاتيكان لفتح مجال الحوار الإسلامي-المسيحي، خاصة بعد التغيرات السياسية والحضارية، التي شهدها منتصف القرن العشرين، والذي كان فيه المجمع الفاتيكاني الثاني نقطة مفصلية في تاريخ دولة الفاتيكان، وتغير نظرتها نحو الإسلام والمسلمين عقديا ودينيا. وبناء على ذلك سنتناول من خلال هذا البحث، أولا التعريف بدولة الفاتيكان ونشأتها ومكانتها الدينية والسياسية في العالم المسيحي، باعتبارها قائد أكبر الطوائف المسيحية عبر العالم، والممثل الأول عن الكاثوليك، وثانيا المجمع الفاتيكاني الثاني وبداية الانفتاح على الحوار الإسلامي المسيحي، والأسس التي قامت عليها هذه المبادرة، وتحليل نقدي لما اشتمل عليه البيان الختامي لمجمع الفاتيكاني الثاني في الجزء المخصص في ضبط العلاقة بين الكنيسة الكاثوليكية والمسلمين This research deals with the Vatican's initiative to open the field of Islamic-Christian dialogue, especially after the political and cultural changes of the mid-20th century, in which the Second Vatican Council was a focal point in the history of the Vatican state, and its view of Islam and Muslims changed doctrinally and religiously . Accordingly, through this research, we will first give the introduction of the Vatican State, its origins and its religious and political status in the Christian world, as the leader of the largest Christian communities around the world, and the first representative of Catholics, secondly the Vatican Council, the beginning of openness to The Christian Islamic Dialogue, the foundations of this initiative, and a critical analysis of what the final statement of the Vatican II Complex included in the section devoted to controlling the relationship between the Catholic Church and Muslims
Statement of the Second Vatican Council and the Islamic-Christian Dialogue Initiative
مقال
Keywords: الفاتيكان ; الحو ار ; الحوار الإسلامي المسيحي ; المجمع الفاتيكاني الثاني; Vatican; dialogue; Islamic-Christian dialogue; the Second Vatican Council